Provisional stenting with side branch rescue stenting is associated with increased 3-year target lesion failure in patients with acute coronary syndrome and coronary bifurcation lesions - Sheiban, Imad; Ge, Zhen; Kan, Jing; Zhang, Jun-Jie; Santoso, Teguh; Munawar, Muhammad; Ye, Fei; Tian, Nailiang; Chen, Shao-Liang (Frontiers in Cardiovascular Medicine, 2022)
Background Provisional stenting (PS) is the main treatment for a majority of coronary bifurcation lesion and includes PS with 1-stent and PS with 2-stent. However, the treatment difference between PS with 1-stent and with 2-stent remains unclear in patients with the acute coronary syndrome (ACS) and coronary bifurcation lesions. Materials and methods Overall, 820 ACS patients with Medina 1,1,1 or 0,1,1 coronary bifurcation lesion who had completed 3-year follow-up were included and assigned to the PS with 1-stent (n = 519) or the PS with 2-stent (n = 301) according to the use of final stenting technique. The primary endpoint was the target lesion failure (TLF) at 3 years since stenting procedures. Results At 3-year follow-up, TLF occurred in 85 (16.4%) patients in the PS with 1-stent group and 69 (22.9%) in the PS with 2-stent group (hazard ratio [HR] 1.52, 95% confidence interval [CI] 1.06–2.17, p = 0.021), mainly driven by a higher rate of target lesion revascularization (TLR) in the PS with 2-stent group (13.0% vs. 8.3%, HR 1.65, 95% CI 1.04–2.61, p = 0.033). Complex bifurcations, side branch (SB) pretreatment, intravascular imaging guidance, and hyperlipidemia were the four predictors for 3-year TLF. SB pretreatment was associated with increased 3-year TLR, leading to an extremely higher 3-year TLF. Conclusion Provisional with 2-stent for patients with ACS is associated with a higher rate of 3-year TLF, mainly due to increased requirement of revascularization. SB pretreatment should be avoided for simple bifurcation lesion.